2023
DOI: 10.1111/cns.14334
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐γ inducible protein 30 promotes the epithelial–mesenchymal transition‐like phenotype and chemoresistance by activating EGFR/AKT/GSK3β/β‐catenin pathway in glioma

Abstract: AimsPrevious studies have indicated that IFI30 plays a protective role in human cancers. However, its potential roles in regulating glioma development are not fully understood.MethodsPublic datasets, immunohistochemistry, and western blotting (WB) were used to evaluate the expression of IFI30 in glioma. The potential functions and mechanisms of IFI30 were examined by public dataset analysis; quantitative real‐time PCR; WB; limiting dilution analysis; xenograft tumor assays; CCK‐8, colony formation, wound heali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…It has been reported that IFI30 can promote the EMT process in glioma cells by activating EGFR/AKT/GSK3β/β-catenin. In addition, IFI30 directly modulates drug resistance in glioma cells [ 17 ]. Fan et al elaborated that IFI30 is highly expressed in breast cancer and is associated with poor prognosis, and that it can affect breast cancer cell proliferation by regulating autophagy [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that IFI30 can promote the EMT process in glioma cells by activating EGFR/AKT/GSK3β/β-catenin. In addition, IFI30 directly modulates drug resistance in glioma cells [ 17 ]. Fan et al elaborated that IFI30 is highly expressed in breast cancer and is associated with poor prognosis, and that it can affect breast cancer cell proliferation by regulating autophagy [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…IFI30 overexpression, which is associated with a poor prognosis in glioma, is positively correlated with tumor grade and may mediate a mechanism of decreased sensitivity to chemotherapy. 25,26 IFN-γ is a key factor in the induction and sustained expression of immune checkpoints in tumor cells of several tumor types including non-small cell lung cancer and skin melanoma, gastric cancer, and glioma. [27][28][29] RIN2 expression increases stepwise in Barrett's esophagus, Barrett's esophagus with dysplasia, and esophageal adenocarcinoma, and it can be used to detect prevalent and inconspicuous heterogeneous hyperplasia and early tumors in Barrett's esophagus.…”
Section: Discussionmentioning
confidence: 99%
“… 4 - 6 Studies have found a correlation between glioma progression and epithelial-mesenchymal transition (EMT), which promotes tumor proliferation, invasion, and treatment resistance. 7 - 9 Therefore, the identification of EMT-related genes associated with glioma invasion is of significant importance for the clinical treatment of gliomas.…”
Section: Introductionmentioning
confidence: 99%